Role of Gut Microbiome in Autism Spectrum Disorder and Its Therapeutic Regulation - Taniya, Masuma Afrin; Chung, Hea-Jong; Al Mamun, Abdullah; Alam, Safaet; Aziz, Md. Abdul; Emon, Nazim Uddin; Islam, Md. Minarul; Hong, Seong-T shool; Podder, Bristy Rani; Ara Mimi, Anjuman; Aktar Suchi, Suzia; Xiao, Jian (Frontiers in Cellular and Infection Microbiology, 2022)
Autism spectrum disorder (ASD) is a neurological disorder that affects normal brain development. The recent finding of the microbiota–gut–brain axis indicates the bidirectional connection between our gut and brain, demonstrating that gut microbiota can influence many neurological disorders such as autism. Most autistic patients suffer from gastrointestinal (GI) symptoms. Many studies have shown that early colonization, mode of delivery, and antibiotic usage significantly affect the gut microbiome and the onset of autism. Microbial fermentation of plant-based fiber can produce different types of short-chain fatty acid (SCFA) that may have a beneficial or detrimental effect on the gut and neurological development of autistic patients. Several comprehensive studies of the gut microbiome and microbiota–gut–brain axis help to understand the mechanism that leads to the onset of neurological disorders and find possible treatments for autism. This review integrates the findings of recent years on the gut microbiota and ASD association, mainly focusing on the characterization of specific microbiota that leads to ASD and addressing potential therapeutic interventions to restore a healthy balance of gut microbiome composition that can treat autism-associated symptoms.